2020
DOI: 10.7150/thno.43968
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue-derived exosomes mitigate the metabolic syndrome in high fat diet mice

Abstract: The ever-increasing incidence of obesity and related disorders impose serious challenges on public health worldwide. Brown adipose tissue (BAT) has strong capacity for promoting energy expenditure and has shown great potential in treating obesity. Exosomes are nanovesicles that share the characteristics of their donor cells. Whether BAT derived exosomes (BAT-Exos) might exert similar metabolic benefits on obesity is worthy of investigation. Methods: Obese mice were established by high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 58 publications
0
82
0
Order By: Relevance
“…Recent studies have shown that miR-22-3p antagonism improves insulin sensitivity and that loss of miR-22 prevents HFD-induced metabolic disorders 45 , 55 . One explanation could be that miR-22-deficient adipocytes might secrete some signaling molecules that potentially activate energy expenditure in other metabolic organs, such as the liver and muscle 56 , 57 . Indeed, fibroblast growth factor 21 (FGF21) is a master metabolic regulator that serves as an important paracrine signaling molecule with remarkable ability to reverse diabetes and obesity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that miR-22-3p antagonism improves insulin sensitivity and that loss of miR-22 prevents HFD-induced metabolic disorders 45 , 55 . One explanation could be that miR-22-deficient adipocytes might secrete some signaling molecules that potentially activate energy expenditure in other metabolic organs, such as the liver and muscle 56 , 57 . Indeed, fibroblast growth factor 21 (FGF21) is a master metabolic regulator that serves as an important paracrine signaling molecule with remarkable ability to reverse diabetes and obesity 58 .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that BAT-derived exosomes contribute to metabolism regulation (reviewed in [ 57 , 58 ]). They can even ameliorate metabolic syndromes in mice with high-fat diet [ 59 ]. Fat tissues, especially BATs, are recognized as important sources of circulating miRNAs, which are involved in regulating gene expressions of other tissues including the liver [ 60 ].…”
Section: The Remaining Mysteries About Batmentioning
confidence: 99%
“…For example, very long-chain acyl-CoA dehydrogenase (ACADVL), an enzyme located in mitochondria, was found to be highly enriched in exosomes derived from BAT. BAT-derived exosomes could transfer ACADVL as a functional protein into liver cells 121 . Thus, the roles of exosomal proteins and lipids in atherosclerosis are emerging research areas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to transporting lipids directly to recipient cells, exosomes can also regulate the expression of classical lipid transporters, such as reverse cholesterol transport mediated by ABCA1 120 . Furthermore, substantial evidence suggests that brown adipose tissue (BAT)-derived exosomes can alleviate lipid accumulation and improve cardiac function, indicating that exosomes are involved in lipid degradation and adipose tissue redistribution 121 . In turn, growing evidence suggests that lipid metabolism affects the biological functions of exosomes, including bioprocesses from signal transduction by receptor-ligand interactions and exosome internalization by or fusion with recipient cells, which provides a new perspective for better understanding the occurrence and development of atherosclerosis 118 .…”
Section: Exosomal Changes Related To Atherosclerosis Risk Factorsmentioning
confidence: 99%